Inhibition of secreted phospholipases A2 by 2-oxoamides based on α-amino acids: Synthesis, in vitro evaluation and molecular docking calculations - Mouchlis, V. D.; Magrioti, V.; Barbayianni, E.; Cermak, N.; Oslund, R. C.; Mavromoustakos, T. M.; Gelb, M. H.; Kokotos, G. (Bioorganic and Medicinal Chemistry, 2011)
Group IIA secreted phospholipase A2 (GIIA sPLA2) is a member of the mammalian sPLA2 enzyme family and is associated with various inflammatory conditions. In this study, the synthesis of 2-oxoamides based on α-amino acids and the in vitro evaluation against three secreted sPLA2s (GIIA, GV and GX) are described. The long chain 2-oxoamide GK126 based on the amino acid (S)-leucine displayed inhibition of human and mouse GIIA sPLA2s (IC50 300 nM and 180 nM, respectively). It also inhibited human GV sPLA2 with similar potency, while it did not inhibit human GX sPLA2. The elucidation of the stereoelectronic characteristics that affect the in vitro activity of these compounds was achieved by using a combination of simulated annealing to sample low-energy conformations before the docking procedure, and molecular docking calculations.